Implementation of Artificial Intelligence in Energy Exploration and Management: A Literature Review - Nur Elah (Journal of Mechatronics and Artificial Intelligence, 2024)
This research examines the utilization of artificial intelligence (AI) in the management and exploration of wind energy potential. Three main areas are discussed: 1) Household Energy Management, where AI-based fuzzy logic systems have proven effective in optimizing the use of electrical appliances and reducing energy consumption, 2) Power Generation Energy Management, where artificial neural network (ANN)-based prediction models are capable of accurately estimating fluctuations in electricity demand to enable better supply planning, and 3) Energy Potential Prediction, where AI algorithms such as Backpropagation Neural Network (BPNN) can predict wind speed with a high degree of accuracy, enabling more reliable estimation of the potential for wind power generation. Overall, this research demonstrates that the integration of artificial intelligence technology has great potential in enhancing energy efficiency and management in the future